PENGARUH PROFITABILITAS, KEPUTUSAN INVESTASI KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hartika, Dela; Norisanti, Nor; Z, Faizal Mulia (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
Research on the effect of profitability, investment decisions, funding decisions and dividend policy on firm value includes several objectives, namely: 1) Knowing the description of variable analysis of profitability, investment decisions, funding decisions, dividend policy and firm value in the property and real estate sector. 2) Knowing the effect between profitability on the value of companies incorporated in the property and real estate sector. 3) Knowing the effect between investment decisions on the value of companies incorporated in the property and real estate sector. 4) Knowing the effect between funding decisions on the value of companies incorporated in the property and real estate sector. 5) Knowing the effect between dividend policy on the value of companies incorporated in the property and real estate sector. The method used in this research is quantitative method with descriptive and associative approaches. The result of this study is that Pofitabilitas on Firm Value does not have a significant effect. Investment Decision on Company Value does not have a significant influence. Funding Decisions on Firm Value do not have a significant effect. Dividend Policy on Firm Value has a significant influence.